2012
DOI: 10.1017/s1092852912000399
|View full text |Cite
|
Sign up to set email alerts
|

Trial-based psychotherapy and the efficacy of trial-based thought record in changing unhelpful core beliefs and reducing self-criticism

Abstract: TBTR may help patients reduce attachment to negative CBs and corresponding emotions. Outcomes were significantly favorable regardless of the format use and therapists' level of exposure to TBTR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 11 publications
3
25
0
1
Order By: Relevance
“…Subsequently, the intensity of patients' dysfunctional CBs and corresponding emotions after the first use of the TBTR was assessed in a larger sample (n = 166) 8 , confirming the previous findings.…”
Section: Introductionsupporting
confidence: 80%
“…Subsequently, the intensity of patients' dysfunctional CBs and corresponding emotions after the first use of the TBTR was assessed in a larger sample (n = 166) 8 , confirming the previous findings.…”
Section: Introductionsupporting
confidence: 80%
“…It is also noteworthy that participants positively compared CFT chair‐work to their prior cognitive treatment, contrasting the chair‐work's “feel‐it” moments to the rational focus of verbal or written work. As identified by participants, it could be argued that CFT chair‐work acts to link “head”‐based propositional meaning with “heart”‐based implicational processing (Teasdale & Barnard, ), giving support to prior findings that chair‐work is more effective at meaning and emotion change than verbal interventions on the same subject (de Oliveira et al, ). The emotional, embodied and multi‐sensory nature of CFT chair‐work might therefore be conceptualised as reducing “rational‐emotional dissociation” (Stott, ) whilst increasing “depth of experiencing” (a factor associated with improved clinical outcomes in experiential practice, for example, Pascual‐Leone & Yeryomenko, ).…”
Section: Discussionsupporting
confidence: 56%
“…Whilst much of the outcome research on chair‐work is preliminary (see Pugh, , for review), technique comparison studies have been notable in demonstrating how chair‐work had a greater impact in reducing mental health problems such as depression, anxiety and self‐criticism when compared to “relationship conditions” alone (Stiegler, Molde, & Schanche, ). Chair‐work has also been shown to outperform written cognitive interventions, in key clinical areas, when addressing the same material (de Oliveira et al, ). Stand‐alone studies of chair‐work have shown particular benefit in targeting and reducing self‐criticism and associated emotional distress (Shahar et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…37 Still regarding the comparison between TBCT or cognitive interventions and BA, in addition to the study by Jacobson et al, 34 another trial has suggested that both psychotherapies have similar efficacy rates. 75 However, TBCT is a transdiagnostic approach, 41,43,46 while BA has been shown to be effective in treating only depression to date. Thus, TBCT might be the choice for patients presenting with comorbid conditions.…”
Section: Discussionmentioning
confidence: 99%
“…40 Therefore, TBCT promotes cognitive restructuring at the 3 levels of cognitive conceptualization (automatic thoughts, underlying assumptions and core beliefs) with techniques that mimic a legal process in which the patients are led to assume the roles of defendant, prosecutor, defense attorney and juror, by seeking evidence for and against their CBs conceptualized as self-accusations. 41,42 TBCT has been shown to be effective in social phobia, 43,44 and also to promote modification of CBs in patients presenting with a variety of psychiatric diagnoses. 43,45,46 It is therefore important to evaluate its efficacy in reducing depressive symptoms relative to BA, a first-line treatment for MDD.…”
Section: Introductionmentioning
confidence: 99%